FACTORS RELATED TO GENERERATIONAL ATITUDES YOUNG IN RICE FARMING IN SUMBER JAYA VILLAGE, KUMPEH ULU DISTRICT MUARO JAMBI REGENCY - Natanail Bukit, Rizky; Muchlis, Fuad; Zakiah, Zakiah (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2025)
The purpose of this research is to: 1) describe the attitude of the younger generation towards rice farming activities; 2) describe the factors related to the younger generation's attitude towards rice farming activities; and 3) analyze the factors related to the younger generation's attitude in rice farming activities in Sumber Jaya Village, Kumpeh Ulu District. The selection of respondents used purposive sampling techniques with a total of 76 young respondents. Data analysis in this research used descriptive analysis with the Chi-square formula. The results of the study indicate that 1) the attitude of the younger generation towards rice farming activities in Sumber Jaya Village, Kumpeh Ulu District, Muaro Jambi Regency is categorized as low. 2) The depiction of education level factors and employment factors outside of farming is categorized as high, while family socialization factors and information from outside the village are categorized as low. 3) The factors that positively relate to the attitude of the younger generation in rice farming activities in Sumber Jaya Village, Kumpeh Ulu District, Muaro Jambi Regency are family socialization factors and information from outside the village, while employment factors outside of farming and education level factors have a negative relationship with the attitude of the younger generation in rice farming activities in Sumber Jaya Village.